2016
DOI: 10.21037/jtd.2016.06.26
|View full text |Cite
|
Sign up to set email alerts
|

Veno-arterial extracorporeal membrane oxygenation for cardiogenic shock due to myocarditis in adult patients

Abstract: Myocarditis is an inflammatory disease of the heart muscle with established histological, immunological and immunohistochemical diagnostic criteria. Different triggers could be advocated as possible etiologies of myocarditis such as viral and non-viral infections, medications, systemic autoimmune diseases and toxic reactions. The spectrum of clinical presentations of myocarditis is broad and varies from subclinical asymptomatic courses to refractory cardiogenic shock. The prognosis of patients with myocarditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
1
35
0
3
Order By: Relevance
“…3 Percutaneous venoarterial extracorporeal membrane oxygenation (VA-ECMO) is often used as first-line MCS because it can be introduced more easily and quickly and is less invasive than other surgical MCS. 4- 6 The management of FM in patients on VA-ECMO support is challenging. Previous studies have reported an in-hospital mortality of 30-50% in these patients.…”
mentioning
confidence: 99%
“…3 Percutaneous venoarterial extracorporeal membrane oxygenation (VA-ECMO) is often used as first-line MCS because it can be introduced more easily and quickly and is less invasive than other surgical MCS. 4- 6 The management of FM in patients on VA-ECMO support is challenging. Previous studies have reported an in-hospital mortality of 30-50% in these patients.…”
mentioning
confidence: 99%
“…46,47 When associated with significant cardiovascular impairment in patients with severe ventricular dysfunction and/or cardiogenic shock, venoarterial ECMO might be considered. 48 ECMO should be initiated before the installation of failure of multiple organs. 49 Specific treatment.…”
Section: Management Of the Patient With Covid-19mentioning
confidence: 99%
“…Najczęściej występuje u młodych osób dorosłych. Od czasu pierwszego zastosowania ECMO przeżywalność pacjentów z piorunującym zapaleniem mięśnia sercowego w trakcie hospitalizacji osiągnęła 55-78% [12]. Kolejnym istotnym wskazaniem do zastosowania zewnątrzustrojowej oksygenacji krwi jest wstrząs pokardiotomijny.…”
Section: Niewydolność Sercaunclassified